PENGARUH SOCIAL MEDIA MARKETING DAN PERSEPSI KUALITAS TERHADAP NIAT BELI SURABAYA SNOWCAKE (Studi pada Masyarakat Surabaya Timur) - NOVILA MILEVA, DINAR; WIDYASTUTI (Jurnal Ilmu Manajemen (JIM), 2018)
Recently there have been many cake business owned by artist in several major cities in Indonesia. They named their business as a souvenir of the city where they do business. They use social media to become a tool for promotion. The purpose of this study is to analyze and discuss the influence of Social Media Marketing and perceived quality of Surabaya Snowcake purchase intentions.The sampling technique used is non-probability sampling with judgmental sampling method. The sample used was 110 people. The respondents used in this study were people of eastern Surabaya with ages ranging from 18 years. Measurement scale uses Likert. The measurement method used is a questionnaire. Data analysis uses the multiple linear regression equation model. The results showed that Social Media Marketing had a positive influence on Surabaya Snowcakes purchase intention, and the perception of quality had a positive influence on Surabaya Snowcakes purchase intention. Keywords: perceived quality; purchase intention; social media marketing